2019
DOI: 10.1002/nme.6139
|View full text |Cite
|
Sign up to set email alerts
|

A stable interface‐enriched formulation for immersed domains with strong enforcement of essential boundary conditions

Abstract: Aims and ScopeThe International Journal for Numerical Methods in Engineering publishes original papers describing significant, novel developments in numerical methods that are applicable to engineering problems. The Journal is known for welcoming contributions in a wide range of areas in computational engineering, including computational issues in model reduction, uncertainty quantification, verification and validation, inverse analysis and stochastic methods, optimisation, element technology, solution techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The standard Lagrange multiplier method caused the boundary locking and oscillation, and some techniques are suggested to overcome it, for example, the enriched formulation 59 . By contrast, the second is to adjust the approximation of the primary variable to let it satisfy the Dirichlet boundary condition exactly, for example, the one proposed by Zheng et al 60 for the element‐free Galerkin method and another approach proposed by van den Boom et al 61 for the discontinuity‐enriched FEM 62,63 . The Nitsche method 58 has received substantial attention recently and has been applied to the meshfree method 64,65 and the partition‐of‐unity methods 66‐71 .…”
Section: Introductionmentioning
confidence: 99%
“…The standard Lagrange multiplier method caused the boundary locking and oscillation, and some techniques are suggested to overcome it, for example, the enriched formulation 59 . By contrast, the second is to adjust the approximation of the primary variable to let it satisfy the Dirichlet boundary condition exactly, for example, the one proposed by Zheng et al 60 for the element‐free Galerkin method and another approach proposed by van den Boom et al 61 for the discontinuity‐enriched FEM 62,63 . The Nitsche method 58 has received substantial attention recently and has been applied to the meshfree method 64,65 and the partition‐of‐unity methods 66‐71 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in this situation, the enriched DOFs are zero, as there is no jump in the gradient of the field in a rigid body displacement of the full element. For more rigorous testing, we place the NURBS interface in an immersed setting, 22 where a material with properties E 1 = 10 and 1 = 0.3 is placed on one side of the interface, and the other side is a void, and the original nodes of the void domain are fixed. This is shown in Figure 7(D)-(I), where we expect, again, to recover three zero-energy modes.…”
Section: Note On Rigid Body Displacementsmentioning
confidence: 99%
“…It has been observed that one factor potentially affecting the accuracy of the computed field gradient is the aspect ratio of the integration elements; 21,22 the creation of enriched nodes too close to existing mesh nodes may result, in some cases, in nonphysical stress concentrations; these are more pronounced near material interfaces 46,47 rather than along Dirichlet boundaries 22 or traction-free cracks. 21 The occurrence of tangent discontinuities or close-to-coincident enriched TA B L E 2 Normalized K I and K II , obtained analytically, with NURBS-based DE-FEM, and with standard DE-FEM…”
Section: F I G U R E 14mentioning
confidence: 99%
See 2 more Smart Citations